2016
DOI: 10.1128/jb.00431-16
|View full text |Cite
|
Sign up to set email alerts
|

The Single Transmembrane Segment of Minimal Sensor DesK Senses Temperature via a Membrane-Thickness Caliper

Abstract: Thermosensors detect temperature changes and trigger cellular responses crucial for survival at different temperatures. The thermosensor DesK is a transmembrane (TM) histidine kinase which detects a decrease in temperature through its TM segments (TMS). Here, we address a key issue: how a physical stimulus such as temperature can be converted into a cellular response. We show that the thickness of Bacillus lipid membranes varies with temperature and that such variations can be detected by DesK with great preci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 39 publications
2
14
0
Order By: Relevance
“…7b clearly show an increase in the diffusion coefficients upon rise in temperature, especially for proteins with smaller number of transmembrane domains. With a membrane thickness h of 2.7 nm [56, 57], we found a membrane viscosity of 1.16 ± 0.43Pa · s at 23 °C, 0.56 ± 0.06Pa · s at 37 °C, and 0.39 ± 0.04Pa · s at 43 °C in good agreement with values in the literature [58]. We also verified that the membrane viscosity decreases with the increasing temperature (inset of Fig.…”
Section: Resultssupporting
confidence: 89%
“…7b clearly show an increase in the diffusion coefficients upon rise in temperature, especially for proteins with smaller number of transmembrane domains. With a membrane thickness h of 2.7 nm [56, 57], we found a membrane viscosity of 1.16 ± 0.43Pa · s at 23 °C, 0.56 ± 0.06Pa · s at 37 °C, and 0.39 ± 0.04Pa · s at 43 °C in good agreement with values in the literature [58]. We also verified that the membrane viscosity decreases with the increasing temperature (inset of Fig.…”
Section: Resultssupporting
confidence: 89%
“…The merged functional TMS was built by fusing 17 residues corresponding to the N-terminus of TM1 with 14 residues of the C-terminus of TM5 and the cytoplasmic catalytic domain of DesK (Figure 1A, right panel). This hybrid construction mimics the full-length protein: it is more active at 25 • C than at 37 • C. As the MS-DesKC lacks an important portion of the TM domain, its regulation is not as tight as that of the full length protein; nevertheless, it allowed us to study at molecular level the mechanism of thermosensing [12,13]. We have demonstrated that a group of Serine residues located towards the C-terminus of TM5 could work as a zipper to transmit the signal [14].…”
Section: Introductionmentioning
confidence: 99%
“…Maintenance of cell membrane homeostasis relies on regulatory proteins that sense and respond to properties such as lipid composition, thickness, compressibility, lateral mobility and curvature [ 1 , 2 ]. The best understood example is perhaps the bacterial multi-pass protein DesK that undergoes a conformational change in response to increased membrane rigidification, resulting in the activation of its kinase domain [ 3 6 ]. Similarly, the yeast single-pass plasma membrane protein Mga2 rotates along its long axis when the surrounding acyl chains are densely packed, also resulting in its activation [ 7 ].…”
Section: Introductionmentioning
confidence: 99%